An integrated facies, diagenesis and geochemical analysis along with sequence stratigraphy of the Lower Triassic Aghe-Darband basin (north-east Iran). (January 2021) - Liaghat, Mohsen; Adabi, Mohammad Hossein; Swennen, Rudy; Mohammadi, Zahra; Alijani, Hassan
Abstract: The Sefid Kuh Formation (Lower Triassic), in Aghe-Darband tectonic window (NE of Iran) reflects a complex setting as is deducible from intercalation of carbonates with volcanic deposits. A detailed sediment petrological, sequence stratigraphical and geochemical study of this formation was carried out to develop a comprehensive knowledge of the complexity in this formation. Field observations of four stratigraphic sections complemented by sediment petrographical analysis led to the identification of microfacies that are grouped into four facies associations. The predominance of tidal flat facies along with oolitic shoal facies and absence of any large barrier/reef features supports the existence of a homoclinal-ramp in an arc basin setting during Sefid Kuh Formation deposition. Calcite cementation and dolomitization are the main diagenetic processes that affected the original strata. Stratigraphic and field studies revealed four 3rd order depositional sequences in this formation which architecture as reflects tectonic control. The measured elemental concentrations (Mn, Sr, Na, Fe, Mg and Ca) along with petrographic studies (e.g. existence of fibrous isopachous cement) suggest aragonite as a precursor mineralogy of the Sefid Kuh carbonates that were deposited in a shallow warm-water subtropical environment. Detailed petrographic and geochemical analysis reflect marine, meteoric and burial diagenetic overprint. Variations in Sr/Ca ratio suggest that diagenetic alteration occurred in an open diagenetic system, with high rock-water interaction. Highlights: The Sefid Kuh Formation, as one of the complex carbonate formations of the Middle East. Depositional environment indicates the a homoclinal-ramp in this formation. Four 3rd order depositional sequences determined in this formation. Geochemical analysis shows open diagenetic system and high water-rock interactions.